Peningkatan Minat Aktivitas Belajar Menggunakan Problem Based Learning Berbasis Kearifan Lokal Siswa Kelas IV - Satriya Herlambang; Siti Anafiah; Siti Muawanah Barozi (Program Studi Pendidikan Profesi Guru, Universitas Sarjanawiyata Tamansiswa Yogyakarta, Indonesia., 2021)
The background of the research is the lack of student interest in problem solving in learning. Thus, students' interest and learning activities tend to be low. The purpose of this research is to use the model problem based learning based on local wisdom to increase students' interest and learning activities. The research method used is the Kemmis and Taggart classroom action research model with action and observation activities carried out at one time. The activity phase consists of planning, implementation, observation, reflection. The results showed that the model problem-based learning based on local wisdom could increase interest and learning activities. Students' learning interest from the initial condition averaged 63 with a percentage of 46.1% increased in the cycle I by an average of 76.5 with a percentage of 77%, and increased in cycle II on average 83 to a percentage of 100%. Student Learning Activity from the cycle I frequency 8 students with a percentage of 61.5% and in cycle II increased to 13 students by a percentage of 100%. Further research is expected to consider learning styles in order to determine the characteristics of each student to design more interesting learning according to student learning styles.